2010
DOI: 10.2135/cropsci2009.11.0690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Alleles at OsAGPS2 and OsSUT1 on the Grain Filling in Extra‐Heavy Panicle Type of Rice

Abstract: Rice (Oryza sativa L.) cultivars of extra‐heavy panicle type (EHPT), which have numerous spikelets in a panicle, often fail to realize their high‐yield potential due to poor grain filling in general, while some EHPTs showed relatively better grain filling. This study first surveyed nucleotide polymorphisms in rice genes possibly related to grain filling, that is, genes for ADPglucose pyrophosphorylase (AGPase) subunits, OsAGPS2 and OsAGPL2, and a sucrose transporter gene, OsSUT1, to clarify the causes underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
(35 reference statements)
0
21
2
Order By: Relevance
“…Kato et al (2010) reported that the same series of nucleotide polymorphisms at this locus was detected in particular cultivars that have numerous spikelets in a panicle (extra-heavy panicle types) and show good grain filling. Therefore, this series of polymorphisms was recognized as a haplotype or an allele for good grain filling, and was designated as AS2-2 (the counterpart allele is AS2-1).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Kato et al (2010) reported that the same series of nucleotide polymorphisms at this locus was detected in particular cultivars that have numerous spikelets in a panicle (extra-heavy panicle types) and show good grain filling. Therefore, this series of polymorphisms was recognized as a haplotype or an allele for good grain filling, and was designated as AS2-2 (the counterpart allele is AS2-1).…”
Section: Introductionmentioning
confidence: 77%
“…This series of polymorphisms in SUT1 was also found in the same cultivars as in the case of AS2 and was regarded as another allele for good grain filling designated as SUT1-2 (the counterpart allele is SUT1-1). The degree of grain filling was significantly better in three cultivars with a double homozygous genotype, AS2-2 SUT1-2, compared with the other three cultivars with AS2-1 SUT1-1 (Kato et al 2010). Interestingly, all of the cultivars with AS2-2 SUT1-2 were indica, whereas those with AS2-1 SUT1-1 were indica or japonica, although only six cultivars were examined.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations